The concept of liquidity in English banking - SAYERS, R.S. (PSL Quarterly Review, 2014)
The article provides a clear synthesis of historical references, factual data, and technical explanations in order to illustrate the complexity of the ideas of liquidity now governing the practice of English bankers. Such complexity is not due only to the changed attitudes towards the rule of “self-liquidating paper”. The fallacy of that principal from the theoretical point of view is undoubted; but its “substantial sense” and “sound basis” at the operative level are still, in the author’s opinion, respectable - being the consequence of the limits of the banker’s experience. The complexity is also evident in the practical application of the “shiftability” principal, and therefore in their attitude towards government paper. The author concludes by focusing attention on the spirit of self-restraint and prudence which governs the present management of English banks in general, and which inspires specifically their concepts of liquidity. JEL: G21